THE INFLUENCE OF CORPORATE GOVERNANCE AND PROFITABILITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE MODERATED BY FIRM SIZE IN THE CONSUMED GOODS INDUSTRIAL COMPANIES ON THE INDONESIA STOCK EXCHANGE - Hutabarat, Metyria Imelda (International Journal of Public Budgeting, Accounting and Finance, 2018)
The issue of corporate social responsibility disclosure or CSRD grows widely. The researches on CSRD find different results.The objective of this research was to analyze the Influence of Corporate Governance and Profitability on Corporate Social Responsibility Disclosure by Firm Size as Moderating. The sample data selected for this research through census technique that was done in Consumed Goods Industrial Companies listed in Indonesia Stock Exchange in the period 2013-2017. The sample was used of this research was 25 Consumed Goods Industrial Companies. The research used software E-views with panel data asthe combination of time series data and cross section. The result of the research showed thatboard of independent commissioners and managerial ownership did not have any influence on corporate social responsibility disclosure, while institutional ownership significant influence on corporate social responsibility disclosure. Board size of commissioners, audit committee, and profitability did not have any influence on corporate social responsibility disclosure, and firm size could not moderate the correlation of corporate governance and profitability on corporate social responsibility disclosure.